2018
DOI: 10.1017/s1742758418000267
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent development of Oenopia conglobata (Col.: Coccinellidae) fed on Aphis gossypii (Hem.: Aphididae)

Abstract: Ladybeetles are known beneficial insects, with a long history in augmentative and classical biological control. The ladybeetle Oenopia conglobata (L.) is a natural enemy of many herbivores, particularly aphids. The temperature-dependent development of O. conglobata was studied at six constant temperatures (22.5, 25, 27.5, 30, 32.5 and 35 °C) to understand its development rate and environmental constraints better. Linear and nonlinear (Lactin) models were fitted to the data. In the thermal range from 22.5 to 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Obviously, the DNA methylation inhibitor (5‐aza‐dC) are broad spectrum, in consideration of multiple subtypes of DNA methyltransferase that have not yet been discovered in oriental armyworm, it is probable that they can affect many MsDnmt s signaling pathways including MsDnmt1 . Temperature change affect the larval development duration, generally the M. separata exhibited longest time from larval to pupae stage under high temperature (Figure 6d), this situation is also consistent with other insects (Jalali, Sakaki, Ziaaddini, & Daane, 2018; Kobori & Hanboonsong, 2017). Besides, injection of DNA methylation inhibitor (5‐aza‐dC) leads to shortened duration time of the last instar to pupae under 36°C (Figure 6d).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Obviously, the DNA methylation inhibitor (5‐aza‐dC) are broad spectrum, in consideration of multiple subtypes of DNA methyltransferase that have not yet been discovered in oriental armyworm, it is probable that they can affect many MsDnmt s signaling pathways including MsDnmt1 . Temperature change affect the larval development duration, generally the M. separata exhibited longest time from larval to pupae stage under high temperature (Figure 6d), this situation is also consistent with other insects (Jalali, Sakaki, Ziaaddini, & Daane, 2018; Kobori & Hanboonsong, 2017). Besides, injection of DNA methylation inhibitor (5‐aza‐dC) leads to shortened duration time of the last instar to pupae under 36°C (Figure 6d).…”
Section: Discussionsupporting
confidence: 87%
“…| 11 of 14 larval development duration, generally the M. separata exhibited longest time from larval to pupae stage under high temperature (Figure 6d), this situation is also consistent with other insects (Jalali, Sakaki, Ziaaddini, & Daane, 2018;Kobori & Hanboonsong, 2017). Besides, injection of DNA methylation inhibitor (5-aza-dC) leads to shortened duration time of the last instar to pupae under 36°C (Figure 6d).…”
Section: Discussionsupporting
confidence: 82%
“…We predicted the occurrence of H. postica at different developmental stages, taking the estimated values of t min and K from the linear model into account, as previously reported 42,43,58,59 . The occurrence of late‐stage larvae at the beginning of the productive cycle (late March) increases the risk of damage caused by this pest 5,29,60,61 .…”
Section: Discussionmentioning
confidence: 98%
“…18 4.5 Phenology and the damage risk period of H. postica in the Ebro basin We predicted the occurrence of H. postica at different developmental stages, taking the estimated values of t min and K from the linear model into account, as previously reported. 42,43,58,59 The occurrence of late-stage larvae at the beginning of the productive cycle (late March) increases the risk of damage caused by this pest. 5,29,60,61 Previous studies have suggested that H. postica produces more than one generation under the conditions in the Ebro basin, 5,29 thus affecting both the first and second alfalfa intercuts.…”
Section: Adult Fitnessmentioning
confidence: 99%